Representasi Perempuan dalam Film Sri Asih Sebagai Superhero di Tengah Kultur Patriaki - Mauludina, Nadiya; Amaliyah, Amaliyah; Dimisqiyani, Erindah; Amalia, Rizky; Aji, Gagas Gayuh (Journal of Educational Research and Humaniora (JERH), 2025)
Indonesia has a long history of patriarchal culture that places men as dominant and often restricts women's freedom of movement. This condition has given rise to gender inequality that persists to this day, making the issue of women's representation in the media, particularly in film, an important topic to examine. This study aims to analyze how the film Sri Asih (2022) represents women as superheroes amidst a patriarchal culture and its implications for the construction of gender roles in society. The study used a qualitative method with a narrative semiotic approach at the levels of reality and representation. Data were obtained through observation of scenes in the film and relevant supporting literature, then linked to theories of representation and feminism to uncover the meaning behind the depiction of Alana/Sri Asih. The results show that Sri Asih is portrayed as a brave, independent woman with the strength to challenge male domination. In various scenes, Alana appears not as a passive object but as an active subject who plays a role in fighting oppression, freeing citizens from exploitation, and becoming a symbol of new hope for society. This representation challenges traditional gender stereotypes that place women in a subordinate position, while also opening up new perspectives on gender equality in the public sphere. This research has had a positive impact in strengthening the understanding that film can be a crucial aspect in fostering collective awareness regarding women's empowerment. Future research could expand the study by comparing the representation of female superheroes in Indonesian and international films to broaden perspectives on gender construction in popular media.